8 A multicentric randomized trial to evaluate the role of uterine manipulator on laparoscopic/robotic hysterectomy for the treatment of low-risk endometrial cancer: the ROMANHY trial (NCT:02762214). (13th November 2020) - Gueli Alletti, S; Perrone, E; Fedele, C; Vizzielli, G; Fagotti, A; Gallotta, V; Rossitto, C; Costantini, B; Restaino, S; Monterossi, G; Fanfani, F; Scambia, G; et al.
Abstract : Background: The role of the intrauterine manipulator in minimally invasive hysterectomy for endometrial cancer has been widely debated in terms of impact on the oncological outcomes. To date, definitive conclusions on the possible advantages and oncological safety of its use in endometrial cancer staging are still awaited. Objectives: This randomized trial aimed to assess the role of the uterine manipulator in terms of oncological and perioperative outcomes in patients undergoing minimally invasive (laparoscopic/robotic) staging for presumed low-risk endometrial cancer. Study Design: Enrolled patients were randomly allocated in two groups according to the use (Group A) or no use (Group B) of the uterine manipulator. The variables collected included baseline demographic characteristics, perioperative data, final pathology report, adjuvant treatment, and follow-up. Results: 154 patients were randomly allocated in Group A (n=78) and Group B (n=76). A statistically significant difference was found in OT for the laparoscopic staging (p=0.005), while no differences were reported for the robotic procedures. The EBL was significantly lower in Group B (p=0.030). Only one conversion to laparotomy (1.3%) occurred in Group A. Comparable results were recorded in terms of peritoneal cytology, LVSI (p=0.584), and pattern of lymphovascular spread (p=0.790). With a median follow-up of 38.7 months, no differences were detected in terms of OS and DFS, and in the number of recurrences. The uterine manipulator had no impact on DFS both at univariate and multivariable analysis. Conclusions: The intrauterine manipulator does not affect the perioperative and oncological outcomes of presumed low-risk endometrial cancer patients undergoing laparoscopic/robotic staging.